2007
DOI: 10.1016/j.ceb.2007.10.004
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms controlling cell cycle exit upon terminal differentiation

Abstract: Coordinating terminal differentiation with permanent exit from the cell cycle is crucial for proper organogenesis, yet how the cell cycle is blocked in differentiated tissues remains unclear. Important roles for retinoblastoma family proteins and Cyclin-dependent kinase inhibitors have been delineated, but in many cases it remains unclear what triggers cell cycle exit. This review focuses on describing recent advances in deciphering how terminal differentiation and exit from the cell cycle are coordinated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
136
3
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 184 publications
(153 citation statements)
references
References 74 publications
9
136
3
1
Order By: Relevance
“…Arrest of or exit from the cell cycle is a precondition for a cell to pass into postmitotic states, such as quiescence, senescence, or terminal differentiation. 37 Studies of murine trophoblast giant cells have shown that terminal differentiation is marked by endoreduplication. 38 However we did not detect an increase in the number of polyploid SGHPL-5 cells after treatment with either CCN.…”
Section: Discussionmentioning
confidence: 99%
“…Arrest of or exit from the cell cycle is a precondition for a cell to pass into postmitotic states, such as quiescence, senescence, or terminal differentiation. 37 Studies of murine trophoblast giant cells have shown that terminal differentiation is marked by endoreduplication. 38 However we did not detect an increase in the number of polyploid SGHPL-5 cells after treatment with either CCN.…”
Section: Discussionmentioning
confidence: 99%
“…This would result in loss of adherence with GBM and with adjacent podocytes, events that are all incompatible with maintaining podocyte function. This is why acquisition of functional specialization in a cell type (or a state of terminal differentiation), such as podocytes, neurons, cardiomyocytes is coupled with the permanent exit from the cell cycle [43] and the arrest in a “postmitotic” state, the molecular bases of which are not completely clarified. Forced re-entry of terminally differentiated cells into the cell cycle is however possible, as demonstrated by a number of experimental manipulations, such as viral infections [44, 45] , overexpression of cyclin D1 and cyclin dependent kinase (CDK)4/6 [46], ectopic expression of the Notch intracellular domain [47], or of elongation factor 2 (E2F) [48], but the consequences are often dramatic.…”
Section: The Podocyte’s Catastrophe: Lost Cell Cycle Controlmentioning
confidence: 99%
“…Arabidopsis E2F target genes have been identified by the presence of a conserved E2F DNA sequence binding motif (Vandepoele et al, 2005;Naouar et al, 2009). In addition, pRB proteins are associated with several chromatin modifying complexes whose targets are less well defined (Buttitta and Edgar, 2007;van den Heuvel and Dyson, 2008) but include genes involved in developmental regulation (Korenjak and Brehm, 2005). The immediate consequences of acute downregulation of RBR at the transcriptional level, however, are not well understood.…”
Section: Gene Expression Regulation By Rbrmentioning
confidence: 99%
“…Retinoblastoma(-like) proteins have been implicated in regulatory decisions, most prominently in the regulation of the G1/S transition via E2F/DP transcription factors, which regulate the expression of cell cycle genes Gruissem, 2007;van den Heuvel and Dyson, 2008), and in loading of DNA replication complexes (Bosco et al, 2001;Mukherjee et al, 2009). RB/E2F complexes have also been found to be associated with developmentally regulated promoters in Drosophila melanogaster, mouse, and Caenorhabditis elegans, often in combination with other transcription factors and chromatin modifiers (Korenjak and Brehm, 2005;Buttitta and Edgar, 2007;van den Heuvel and Dyson, 2008). In addition, RB has been implicated in E2F-independent regulatory mechanisms, including direct interaction with subunits of the anaphasepromoting complex during cell cycle exit (Binne et al, 2007).…”
Section: Rbr Homeostasis Is Critical For Meristem Integrity and Functionmentioning
confidence: 99%